2015
DOI: 10.1097/mol.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Improving the cost-effectiveness equation of cascade testing for familial hypercholesterolaemia

Abstract: Purpose of reviewMany international recommendations for the management of familial hypercholesterolaemia propose the use of cascade testing using the family mutation to unambiguously identify affected relatives. In the current economic climate DNA information is often regarded as too expensive. Here, we review the literature and suggest strategies to improve cost-effectiveness of cascade testing.Recent findingsAdvances in next-generation sequencing have both speeded up the time taken for a genetic diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Patents have expired on some high-intensity statins used to treat FH, leading to substantial cost reductions, while next generation sequencing has reduced the cost of DNA tests. There is now convincing evidence that in patients with a clinical diagnosis of FH but no mutation in any of the three known FH-causing genes ( LDLR , APOB , and PCSK9 ), 9 , 10 the most likely cause of elevated LDL-C is polygenic. 11 In polygenic FH the risk of relatives having significantly raised LDL-C is much lower 12 than the 50% observed for monogenic hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Patents have expired on some high-intensity statins used to treat FH, leading to substantial cost reductions, while next generation sequencing has reduced the cost of DNA tests. There is now convincing evidence that in patients with a clinical diagnosis of FH but no mutation in any of the three known FH-causing genes ( LDLR , APOB , and PCSK9 ), 9 , 10 the most likely cause of elevated LDL-C is polygenic. 11 In polygenic FH the risk of relatives having significantly raised LDL-C is much lower 12 than the 50% observed for monogenic hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the screening of lipid disorders in children has been discussed. While some authors recommended the cascade screening (screening the children with a family history of early atherosclerotic disease or high cholesterol level), some studies suggested the universal screening in pediatric age group [2][3][4][5]. Oppositely, US Preventive Services Task Force concluded that there is insufficient evidence for the screening of dyslipidemia in those aged less than 20 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pedigrees and mutations were registered in a database, and whenever a new index was identified, the database was checked to see if this person might be related to a known family in the database, so genetic testing could be personalized. The program was found to be cost-effective [ 13 ]. The programme had always been regarded as a project, and when it started, it was expected that most carriers would have been detected by 2010, based upon an estimated heterozygote frequency of 1:500.…”
Section: Introductionmentioning
confidence: 99%